HARGA POKOK PRODUKSI DAN METODE COST PLUS PRICING : STUDI KASUS PADA USAHA MIKRO KIOS MARIBEL - Kotambunan, Julia Sherina; Mawikere, Lidia M.; Suwetja, I Gede; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
Cost of goods manufactured refers to the expenses incurred by a company to produce goods or services. The cost-plus pricing method is a pricing strategy where the selling price is determined by adding the desired profit margin to total cost of production and marketing the product in the future. This study aims to analyze the cost of goods manufactured in determining the selling price using the cost-plus pricing method. This is a qualitative research with a descriptive approach. The data sources used are primary data, collected through observation, interviews, and documentation. The research findings indicate a difference between the selling price calculated by company compared to the selling price by using the cost-plus pricing method with full costing approach. Two samples were used here are steamed buns with meat filling and steamed buns with mung bean filling. The difference in selling price calculations using the cost-plus pricing method was 33.04% and 12.83% higher, respectively. This discrepancy is due to the company’s incomplete calculations, relying only on market prices and the owner’s estimation.